PENGARUH TENAGA KERJA, JAM KERJA DAN TINGKAT HARGA TERHADAP TINGKAT PRODUKSI INDUSTRI BATU BATA DI DESA PULAU PINANG KECAMATAN BINUANG KABUPATEN TAPIN - ADAM RASIDI; MUZDALIFAH MUZDALIFAH (PPJP Universitas Lambung Mangkurat, 2019)
This research aims to determine what the influence of labor, working hours and price levels on the level of production of the brick industry in Pulau Pinang Village, Binuang Sub-district, Tapin District and the most dominant factor of the three factors.This research uses data analysis tools in the form of software Eviews 9, with multiple linear regression models using the least squares estimation method. The data used are primary and secondary data. The results of the research show that labor, working hours and price levels have a significant effect on the level of production both silmutaneously and partially. The factor that shows the most dominant influence in influencing the level of production of the brick industry is the labor factor.Keywords: Influence; Labor; Working Hours; Price Levels; Production Levels